HR strategy : creating business strategy with human capital - Kearns, Paul (Elsevier/Butterworth-Heinemann, 2010)
Focusing on HR as a key driver of competitive advantage and sustainable success, this edition demonstrates how to create a winning human resource strategy by predicting the results you expect to see and developing a workable, measurable plan for managing human capital